Media Representation of Tutoring as a Phenomenon of Pedagogical Discourse - A. D. Efimova (Научный диалог, 2024)
The aim of this study is to explore the media representation of tutoring as a phenomenon within pedagogical discourse. An analysis of a thematic corpus of texts reveals that the imported concept of TUTORING acquires new conceptual features that reflect the linguistic and cultural specificity of its interpretation in the Russian-speaking media landscape. Distinctive characteristics of the media representation of the conceptual education of TUTOR are established in comparison with traditional pedagogical professions and its definition in professional standards. It is demonstrated that in the Russian-speaking media discourse, tutoring is perceived by the professional discursive community as a profession of the future, tasked with shaping individuals capable of addressing the global challenges of modernity. Evaluative characteristics of the phenomenon of TUTORING are identified, reflecting its perception by both the professional discursive community and a broader readership. In the former case, positive evaluations prevail, characterized by notions of ‘assistance’ and ‘support’; in the latter, negative evaluative traits emerge, associated with skepticism towards tutoring. Figurative-perceptual characteristics of tutoring are presented, expressed through metaphorical strategies based on source domains such as “Sport,” “Journey,” and “Nature.” The study of the phenomenon of tutoring underscores the significance of the discursive factor in understanding the concept.